L'Europe, l'évaluation technologique et la régulation fractale mondiale - Giesen, Klaus-Gerd (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1995)
The study attempts to make a theoretically informed analysis of technology assessment (TA) as part of postfordist global governance. It focuses first on the FAST programme of the EC, designed to regulate the relationship between producers of new technologies (industry, states) and civil society. The author shows that this regulation, based on the expertise of the social sciences, is largely asymmetrical in favour of the former and an attempt to engineer social consensus at the supranational level. The focus shifts then downwards to the numerous national and regional TA institutions in Western Europe which are all parts of a FAST dominated transnational network, as well as upwards to various related global TA activities (OECD, Lisbon Group, etc.). These different levels of analysis demonstrate that TA is politically constructed as a polycentric, non-hierarchical web of interrelated regulation mechanisms. As such, it is argued, it steadily permeates and recombines existing political structures and levels in order to meet as quickly as possible precise demands of legitimization and accumulation, and should therefore be called a « fractal » regulation.